Outcomes of mechanical circulatory support for acute myocardial infarction complicated by cardiogenic shock. Issue 3 (22nd June 2021) - Kim, Yeunjung; Shapero, Kayle; Ahn, Shawn S.; Goldsweig, Andrew M.; Desai, Nihar; Altin, S. Elissa
Abstract: Background: Mechanical circulatory support (MCS) with the Impella device (Abiomed, Danvers, MA) has been associated with higher in‐hospital mortality than intra‐aortic balloon pump (IABP) in the Premier Healthcare Database and National Cardiovascular Data Registry. Methods: The objective of this retrospective cohort study was to describe trends and outcomes of Impella usage in acute myocardial infarction complicated by cardiogenic shock (AMICS) treated with MCS (Impella or IABP) using real‐world observational data from the National Inpatient Sample (NIS) including hospitalizations for AMICS managed with MCS between January 2012 to December 2017. The primary outcomes included in‐hospital mortality, transfusion, acute kidney injury, stroke, total costs, and length of stay. Propensity score matching was performed with hierarchical models using risk factor and Elixhauser comorbidity variables. Results and Conclusion: We identified 54, 480 hospitalizations for AMICS managed with MCS including 5750 (10.5%) utilizing Impella. Throughout the study period, Impella usage increased yearly to 19.9% of AMICS cases in 2017. After propensity score matching, Impella was associated with higher in‐hospital mortality (odds ratio [OR] 1.74, 95% confidence interval [CI] 1.41–2.13) and transfusions (OR 1.97, 95% CI 1.40–2.78) than IABP, without association with acute kidney injury or stroke. Impella use was associated with higher hospital costs (mean difference 22, 416.80 [95% CI 17, 029‐27, 804]). Impella usage for AMICS increased significantly from 2012 to 2017 and was associated with increased in‐hospital mortality and costs. Randomized controlled trials are urgently needed to assess the safety and efficacy of Impella.